2018
DOI: 10.1038/s41419-018-0887-0
|View full text |Cite
|
Sign up to set email alerts
|

PAK2–c-Myc–PKM2 axis plays an essential role in head and neck oncogenesis via regulating Warburg effect

Abstract: The histone modifiers (HMs) are crucial for chromatin dynamics and gene expression; however, their dysregulated expression has been observed in various abnormalities including cancer. In this study, we have analyzed the expression of HMs in microarray profiles of head and neck cancer (HNC), wherein a highly significant overexpression of p21-activated kinase 2 (PAK2) was identified which was further validated in HNC patients. The elevated expression of PAK2 positively correlated with enhanced cell proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 72 publications
1
53
0
Order By: Relevance
“…Studies have shown elevated expression of PAK2 resulting in an alteration of histone modification, thereby regulating gene expressions also. Differential expression levels of PAK2 have been reported in various malignancies including breast, gastric, hepatocarcinoma and head, and neck cancer (28,29). Elevated levels of PAK2 have been reported in castration-resistant tumors and the knockdown experiments further revealed that PAK2 can regulate colony formation and invasion experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown elevated expression of PAK2 resulting in an alteration of histone modification, thereby regulating gene expressions also. Differential expression levels of PAK2 have been reported in various malignancies including breast, gastric, hepatocarcinoma and head, and neck cancer (28,29). Elevated levels of PAK2 have been reported in castration-resistant tumors and the knockdown experiments further revealed that PAK2 can regulate colony formation and invasion experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the oncogene Myc, which includes c-Myc, N-Myc, and L-Myc, plays an important role in aerobic glycolysis in HCC as well. C-Myc is reported to overexpressed in HCC, and can promote the Warburg effect by increasing the expression of glycolytic related markers, such as GLUT1, LDH and PKM2 [66][67][68][69]. Conversely, c-Myc can also be regulated by PKM2 in the nucleus, for PKM2 can translocate into nucleus and act as a coactivator of β-catenin to induce c-Myc expression, leading to the expression of c-Myc targeted genes [30,67].…”
Section: Discussionmentioning
confidence: 99%
“…(with prognostic efficacy), all of which were previously identified to play a major role in head and neck oncogenesis as well as in other cancers [45][46][47][48][49][50][51][52] EPS8, identified in ECS-laryngopharyngeal patients in this study, is known to be involved in the proliferation apoptosis, adhesion and migration in other cancers including HNSCC [53][54][55][56]. The correlation of these markers with the clinically/pathologically classified sub-cohorts (ALI+/PNI+) indicated their possible relevance as predictive panel, with a subset of genes providing survival impact.…”
Section: Discussionmentioning
confidence: 99%